Tanggung Jawab Pelaku Usaha Terhadap Konsumen - Itra Saleh; Nur Mohamad Kasim; Dolot Alhasni Bakung (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
In this study the authors examined consumer protection against business actor defaults. This is motivated by the reality that occurs in society that there are several business actors who do things that harm consumers. Consumer rights are often ignored by business actors, in other words, business actors have not fulfilled their obligations to consumers properly. Consumers who feel aggrieved by business actors can submit a lawsuit to BPSK, but often consumers cannot accept the judge's decision so they proceed to the appeal level, namely at the District Court. From this background, the authors formulate several problems, namely what are the legal rules regarding consumer dispute resolution and what are the responsibilities of business actors towards consumers. This research is a type of field research that is descriptive in nature. In this study, 2 (two) data sources were used, namely primary data, which was data obtained directly from respondents through field interviews or research locations, and the second was secondary data, namely data obtained or collected through some literature or literature studies. There are 2 (two) data collection methods used in this study, namely observation and interviews. The results of this study indicate that consumer protection at BPSK is in accordance with the provisions of Law number 8 of 1999 concerning consumer protection, while the district court is less objective in resolving consumer disputes. The responsibility of business actors in default can be carried out by continuing/canceling the agreement and compensating for losses incurred as a result of the default.